Redesain Taman Rekreasi Kota Malang Berbasis Taman Bermain Anak - Mali, Benyamin Arkadius; Setyabudi, Irawan; Alfian, Rizki (Aksen : Journal of Design and Creative Industry, 2021)
A city park is an open space in an urban area that functions as a balance between nature and greenery andhuman activities, such as recreation or a place to rest from daily activities. This condition requires a gardendesign that provides comfort, so it needs vegetation and other facilities supporting street furniture. Openspace in public facilities is called public open space and includes green open space (RTH). The function ofRTH is to improve the quality of life of urban communities, encourage the creation of public space activitiesfor the community, add aesthetic value to urban areas, create a comfortable atmosphere for pedestrians,and so on. The focus of the study in this research is on the City Recreation Park (tarekot), which is located inthe center of Malang city, not far from Tugu square. The condition of the park, in general, has not undergonemuch development, so there has been no increase in the number of visitors. The problem is the pattern ofless functional space for visitors (especially children), the lack of a level of security because this park islocated beside a river, there is no division of games based on age. A garden will be safe and comfortable forthe broader community if facilities are provided for children to play in the playground. This research limits theprovision of facilities for children. The research method used is a design method with a thinking approachfrom Gold (1980), Hakim (2012), and Setyabudi (2016). The results of this study are the results of a proposedredesign with the concept of a children’s playground. Keywords: City Park, Green Open Space, Suitable for Children, Redesign